Kesadaran Sosial Dalam Pemikiran Nietzsche: Tinjauan Dalam Proses Pengembangan Masyarakat di Indonesia - Derry Ahmad Rizal; Ahmad Kharis (UIN Siber Syekh Nurjati Cirebon, 2022)
This article discusses the social consciousness that every human being should have. Community development in the realm of science and practice has awareness in a change, exploring the potential so that the community can grow for the better. Friedrich Williams Nietzsche,a philosopher who was considered extreme in his thinking, thus gave rise to pros and cons. God Is Dead or God Is Dead is a long conversation. According to the word Zarathusta, Nietzsche's work on God is dead. God has been killed, showing an act of making changes and growing awareness in society. The method used is qualitative descriptive with literature studies and tracing case studies related to community development. The results of the research obtained in every community development practice with various models such as tourism, economy and others require public awareness to move. With such understanding every community can grow and be independent in building villages and cities. As Nietzsche explained, it is only a network of human relationships and it is only under such conditions that consciousness develops.